PENGARUH MEDIA PROMOSI LEAFLET TERHADAP PENGETAHUAN IBU TENTANG IMUNISASI DASAR PADA ANAK DI POSYANDU RW 08 DESA BOJONGKULUR KABUPATEN BOGOR TAHUN 2022 - Faradilla, Intan Tita; Nina, Nina; Novita, Astrid (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
Immunization is the government's effort to prevent infants and toddlers from contracting infectious diseases so that the incidence of infection will decrease and reduce disability and death rates. The low level of immunization in children is partly due to the lack of education and knowledge of mothers about the importance of complete basic immunization, the lack of knowledge of mothers is caused by the lack of implementation of health promotion and the media used for health promotion is still not appropriate. This study aims to determine the effect of leaflet promotion media before and after being given an intervention. This type of research uses quantitative methods with a quasi-experimental approach. The design used in this research is one group pre-test and post-test. The sample of this research is mothers who have toddlers aged 0-24 months as many as 30 respondents. The results showed that the pre-test average value was 53.3 while the post-test average was 89.2. The results of the analysis based on the Paired Sample t-test obtained P – value = 0.000 where α < 0.05, which means there was a significant difference in the level of mother's knowledge before being given treatment and after being given treatment with leaflet promotional media. It can be concluded that targeted health promotion media are needed to increase mothers' knowledge of complete basic immunization in children aged 0-24 months at Posyandu RW 08 Bojongkulur Village, Bogor Regency. The researcher's suggestion is to hold special training in making health promotion media for health promotion workers so that they can be used and developed as health education media